Web-Based Corporate Environmental Reporting in Nigeria: A Study of Listed Companies - Uwalomwa UWUIGBE (Informatică economică, 2012)
This paper basically examined the utilization of the Internet for communicating corporate environmental information by listed financial and non-financial companies in Nigeria. The sample for the study consists of 30 firms listed on the Nigerian stock exchange. While the content analysis technique was used as a basis for eliciting data from the corporate websites of the selected firms, the student t-test statistics was used to find out whether there is a significant difference in the level of web-based corporate environmental disclosure between financial and non-financial firms in Nigeria. In addition, the linear regression method of data analysis was employed to investigate whether there is a relationship between the financial performance of firms and the level of corporate environmental disclosures of the selected listed firms in Nigeria. The paper as part of its findings observed that there is no significant difference in the level of web-based corporate environmental disclosure between listed financial and non-financial firms in the Nigeria stock exchange